2013
DOI: 10.7567/jjap.52.09ka01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bipolar Pulse Poling on the Ferroelectric and Piezoelectric Properties of Tetragonal Composition Pb(Zr0.3,Ti0.7)O3 Thin Films on Microelectromechanical Systems Microcantilevers

Abstract: We have investigated the effects of bipolar pulse poling (pulse poling) on the crystal orientation, ferroelectric property and piezoelectric property of Pb(Zr0.3,Ti0.7)O3 (tetra-PZT) thin films integrated on MEMS-based microcantilevers. 1.9-µm-thick tetra-PZT thin films were deposited by the sol–gel technique and fabricated into piezoelectric microcantilevers by a MEMS microfabrication process. We have found that the suitable step for pulse poling in the MEMS microfabrication process is after the completion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The other difference is that |d 31 | of MPB-PZT thin films increases with pulse poling voltage. As we reported in the previous study, 14 the |d 31 | of tetra-PZT thin films reaches its maximum at the bipolar pulse poling voltage of 50-60 V (26.4-31.6 kV/cm) in spite of gradual increase in degree of c-axis orientation. Note that the dependence of |d 31 | on the pulse poling electric field (not the voltage) may be similar for thin films thicker than 0.5 µm, which are typically used for piezoelectric MEMS.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The other difference is that |d 31 | of MPB-PZT thin films increases with pulse poling voltage. As we reported in the previous study, 14 the |d 31 | of tetra-PZT thin films reaches its maximum at the bipolar pulse poling voltage of 50-60 V (26.4-31.6 kV/cm) in spite of gradual increase in degree of c-axis orientation. Note that the dependence of |d 31 | on the pulse poling electric field (not the voltage) may be similar for thin films thicker than 0.5 µm, which are typically used for piezoelectric MEMS.…”
Section: Resultssupporting
confidence: 72%
“…[11][12][13] Recently, we have found that bipolar pulse poling, where intermittent ac triangle wave larger than coercive field of the PZT thin films is applied, enhances the piezoelectric property of tetragonal composition (Zr/Ti = 30/70) PZT (tetra-PZT) thin films. 14 In the previous study, we have fabricated piezoelectric microcantilevers using 1.9-µm-thick tetra-PZT thin films. It has been found that the suitable process step for bipolar pulse poling is after completion of the MEMS microfabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…3 suggests that one could obtain higher strain by using pure tetragonal PZT and transiting from 100% a-domains to 100% c-domains by applying voltage. However, Kobayashi et al have recently observed that this complete a to c-domains transition in pure tetragonal PZT 30/70 requires large electric field (0.4 MV/cm) and induces cracks into PZT [20]. This result suggests that only PZT compositions in an MPB zone provide sufficient polarization mobility to take advantage of phase transitions to enhance piezoelectric properties.…”
Section: Fig 3: θ -2θ Profile Evolution Of Pzt Around Peak (400) Vs D...mentioning
confidence: 99%
“…[9][10][11][12] On the other hand, the inorganic ferroelectric films have been widely utilized because of their superior properties their flexibility is very poor because they are usually prepared on the rigid substrates. [13][14][15] One of the most promising ideas to realize the high performance flexible devices having ferroelectricity and piezoelectricity is to combine inorganic ferroelectric films and organic substrates.…”
Section: Introductionmentioning
confidence: 99%